Development of a new trend conjugate vaccine for the prevention of Klebsiella pneumoniae - Tarek A. Ahmad; Medhat Haroun; Ahmed A. Hussein; El Sayed H. El Ashry; Laila H. El-Sayed (MDPI AG, 2012)
Klebsiella pneumoniae is a major cause of nosocomial pneumonia, septicemia and urinary tract infections, especially in newborns, blood cancer patients, and other immunocompromised candidates. The control of K. pneumoniae is a complicated issue due to its tight pathogenesis. Immuno-prophylactic preparations, especially those directed toward the bacterium O-antigen, showed to be the most successful way to prevent the infection incidence. However, all previously proposed preparations were either of limited spectrum or non-maternal, and hence not targeting the main Klebsiella patients. Moreover, all preparations were directed only to prevent the respiratory diseases due to that pathogen. This article addresses the development of a method originally used to purify the non-capsular bacterial- endotoxins, as a new and easy method for vaccine production against K. pneumoniae. The application of this method was preceded by a biotechnological control of capsular polysaccharide production in K. pneumoniae. The new produced natural conjugate between the bacterial O-antigen and its outer membrane proteins was evaluated by physicochemical and immunological methods to investigate its purity, integrity, safety and immunogenicity. It showed to be pure, stable, safe for use, and able to elicit a protective immunoglobulin titer against different Klebsiella infections. This immune-response proved to be transferable to the offspring of the vaccinated experimental rabbits via placenta.